Women in the Jātakas: Categories of Representation and the Subject of Sexuality - ROHA ROMSHA (जम्बूद्वीप - the e-Journal of Indic Studies (ISSN: 2583-6331), 2024)
In the stories of Jātakas, one encounters plethora of evidences concerning womanhood. Most stereotype women as immoral creatures, while some valorise them for their caregiving and selfless nature. Yet another set of stories depict women in a neutral light, associating no explicit imagery with their existence. The variety in representation of women in the Jātakas has to be studied in view of the stories’ unique position in the Ancient Indian literature. As folktales, Jātakas reflected the multifaceted social reality. While on account of their Buddhist linkages, they had to strike a balance between the canonical insistence on celibacy and Buddhism’s popular call for egalitarianism